Analisa Determinan Sosial Demografi Ibu Terhadap Kejadian Stunting pada Anak Usia Toddler di Wilayah Puskesmas Kenjeran Surabaya - Diyah Arini; Nur Chabibah; Martha Ayu Agustin (Fakultas Ilmu Kesehatan, 2020)
ABSTRACT Analysis of Determinants of Social Demographics in the kenjeran District Health Center Surabaya. A Mother’s social demography are the most underlying thing for children’s health, growth and development as well as being one of the causes of stunting. Research aims to analyze the social demographic with stunting in toddler-aged children in the Kenjeran Health Center area of Surabaya. The Research design is a cross-sectional method with 152 samples, thepopulation is the mother of toddlers. That is divided into two groups, 76 stunting toddlers and 76 normal toddlers. Data collecting is using questionnaire sheets. Data analysis using logistic regression test. Based on logistic regression test, there was a significant relationship between the level of maternal age (ρ=0,005) OR 3.778, maternal height (ρ=0,003) OR 5.676, maternal BMI (ρ=0,000) OR 4.528, meanwhile, there is no relationship between the numberof familly (ρ=0,735) OR 1.160, maternal education (ρ=0,999) OR 3.701, and family income (ρ=0,078) OR 2.224 dan pekerjaan ibu (ρ=0,999) OR 0.000 with the incidence of stunting in toddler age children in the Kenjeran Health Center area of Surabaya. The dominant social demographic factor affecting the stunting event is the BMI when the mother is pregnant with a degree of significance ρ=0,000 OR 4.528. Early agr handling is required to prevent the event of stunting on children, such as anthropometric measurements on children, providing high nutritional foods, and health education for adolenscent girls and pregnant women about reproductive health for fetal. keyword: Stunting, Mother’s , Social demography, toddler